Building a Qurani Society: A Collaborative Community Base Research - Slamet Riyadi; Febby Adinda; Febrianti Dewi; Hazimah; Kharismahate Bengi; Miftahussa’adah Irfani; Sri Utari (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
Pondok Tahfidz Quran Huurun'Iin is a non-formal educational institution specifically for girls, which is located on Jalan Masjid al-Barokah, Marindal I 19B, Deli Tua Timur, Deli Serdang, North Sumatra. Built-in January 2021 in a Muslim-majority environment, however, it seems far from Islamic values. Concern for the condition of the community around the location, especially the younger generation, has encouraged Pondok Tahfidz Quran Huurun'Iin to fill the role of Quran education through non-formal channels. This potential encourages the STAI As-sunnah Arabic Language Education study program to collaborate with Pondok Tahfidz Quran Huurun'Iin in a community service program with the theme "the Quran." This activity aims to improve the ability to memorize the Al-Qur’an and Arabic and optimize the month of Ramadan with entire interaction with the Al-Qur’an. The method used is Community Base Research (CBR), laying down the basic principles, planning, collecting, analyzing data, and acting on findings. As a result, STAI As-sunnah and Pondok Tahfidz Al-Qur’an Huurun'Iin succeeded in developing Arabic language learning as an alternative to filling youth activities around the Pondok Tahfidz Al-Qur’an Huurun'Iin location and gradually coloring the environment with a more Islamic and Quranic style.